The Day After Tomorrow : Designing an Optimal Fiscal Strategy for Libya - Caceres, Carlos (IMF Working Papers; Working Paper ;, 2013)
Libya is highly dependent on exhaustible and volatile hydrocarbon resources, which constitute the bulk of government revenues. Although resource wealth provides the means to promote socio-economic development, procyclical fiscal policies threaten macroeconomic stability as well as fiscal sustainability and intergenerational equity. In three parts, this paper provides an assessment of the cyclically adjusted fiscal stance, analyzes fiscal sustainability according the permanent income framework, and simulates various fiscal policy rules with the objective of developing a rule-based fiscal strategy that would delink the economy from oil price fluctuations, improve the management of resource wealth, and safeguard macroeconomic stability.